- KESEJAHTERAAN ANAK ATAS MENINGKATNYA KASUS PENGAJUAN DISPENSASI NIKAH DI DESA CIKAWUNG KECAMATAN TERISI KABUPATEN INDRAMAYU - Mega Ningrum; Wahyuni Retnowulandari (Reformasi Hukum Trisakti, 2023)
The rise of child marriage is a serious issue for child welfare, whether children can be said to be prosperous. It is impossible to isolate Indonesia's practice of child marriage from the social, cultural, and economic circumstances that shape society, such as the underage marriage that takes place in Cikawung Village, Indramayu Regency. what is the background to the increase in underage marriages in Cikawung Village, Terisi subdistrict, Indramayu Regency, as well as whether children who marry underage become prosperous and what efforts are made by parents, the community and the government? Sociological legal research is the kind of research that is employed. The research is of a descriptive character. The deductive approach to conclusion-making. There were several variables that contributed to the rise in marriage dispensation in Cikawung Village. Law Number 16 of 2019 is one of the reasons for this, along with culture, parenting, economics, education, and free association. In Cikawung Village, underage marriage leads to unfavorable welfare circumstances for kids and violates Law Number 4 of 1979; instead, kids should be playing, attending school, or pursuing their creative endeavors while also keeping in mind their little households. The lack of growth and direction for child welfare initiatives is the reason why parents, society, and the government are not doing more to stop the rise in underage marriages.